Pola Asuh dan Kejadian Balita Stunting di Puskesmas Lelea Kabupaten Indramayu - Delfian Rahmat Aditia; Zulmansyah; Herry Garna (Bandung Conference Series: Medical Science, 2024)
Abstract. Stunting is a condition where the physical height or body length of a toddler is not appropriate compared to his/her peers with a score of less than -2SD. In West Java, the prevalence of stunting is 31.1%. Internal factors causing stunting are maternal and toddler nutritional intake, health status, parenting style, food quality and maternal employment. External factors are health services and parenting patterns for toddlers. Parenting is the behavior of parents in guiding them to provide love, attention and support for the development and growth of toddlers. Workers are classified based on the duration of work in one week, workers who work more than 35 hours/8 hours a day in one week are referred to as full-time workers. Workers who work less than 35 hours in 1 week are referred to as incomplete workers. This study aims to analyze the relationship between parenting patterns of full-time working mothers and the incidence of stunting in toddlers at the Lelea Community Health Center, Indramayu Regency. Abstrak. Stunting merupakan keadaan fisik tingi atau panjang tubuh balita tidak sesuai dibanding dengan usia sebayanya dengan score kurang dari -2SD, di Jawa Barat prevalensi stunting 31,1%. Faktor penyebab stunting faktor internal adalah asupan gizi ibu dan balita, status kesehatan, pola asuh, kualitas pangan dam pekerjaan ibu. Faktor eksternal adalah pelayanan kesehatan dan pola asuh balita. Pola asuh merupakan perilaku orangtua dalam membimbing memberikan kasih sayang, perhatian, serta sokongan untuk perkembangan dan pertumbuhan balita. Pekerja diklasifikasikan berdasarkan durasi kerjanya dalam satu minggu, pekerja yang bekerja lebih dari 35 jam/ 8 jam sehari dalam satu minggu disebut sebagai pekerja penuh waktu. Pekerja yang bekerja kurang dari 35 jam dalam 1 minggu disebut sebagai pekerja tidak penuh. Penelitian ini bertujuan menganalisis hubungan pola asuh ibu pekerja penuh waktu dengan kejadian balita stunting di Puskesmas Lelea Kabupaten Indramayu.